(untitled) (Lafia Journal of Scientific and Industrial Research, 2023)
Renewable energy, specifically wind power, is vital for reducing fossil fuel dependency, greenhouse gas emissions, and improving energy security. With advancements in technology, wind energy has become cost-effective and competitive. Wind energy research in Lafia is essential to developing solutions in harnessing its potential as a significant renewable energy source for Nigeria, which has abundant but untapped wind energy resources. This study investigates the wind energy potential in Lafia, Nasarawa State, using daily averaged wind speed data from MERRA-2 measured at 2, 10, and 50-metre altitudes. The Weibull distribution function was applied to determine Lafia’s wind energy potential, and the outcomes revealed that the highest yield for wind harvest occurred during the peak of the dry season in February, while the lowest yield for wind harvest occurred during the beginning of the dry season in October. Moreover, the monthly mean power densities peaked in February, 2001 at 341.87 W/m2 (class 3: 300 < PD ≤ 399), indicating moderate potential, and in January, 2002 at 454.12 W/m2 (class 4: 400 < PD ≤ 499), indicating good potential. However, the peak monthly mean power densities in December, 2003 and February, 2004 were poor and marginal, respectively, according to the Wind Resource Potential (WRP) classification. Furthermore, at 50 metres altitude, the recorded wind speeds were above the recommended minimum (3.00 – 4.00 m/s) for most wind turbines to start producing electricity. The findings indicate significant wind resource potential at high altitudes (50 metres) in Lafia, which suggests great potential for wind energy generation.